Linguistic Experiments and Ordinary Language Philosophy. (December 2015) - Hansen, Nat; Chemla, Emmanuel
Abstract J.L. Austin is regarded as having an especially acute ear for fine distinctions of meaning overlooked by other philosophers. Austin employs an informal experimental approach to gathering evidence in support of these fine distinctions in meaning, an approach that has become a standard technique for investigating meaning in both philosophy and linguistics. In this paper, we subject Austin's methods to formal experimental investigation. His methods produce mixed results: We find support for his most famous distinction, drawn on the basis of his 'donkey stories', that 'mistake' and 'accident' apply to different cases, but not for some of his other attempts to distinguish the meaning of philosophically significant terms (such as 'intentionally' and 'deliberately'). We critically examine the methodology of informal experiments employed in ordinary language philosophy and much of contemporary philosophy of language and linguistics, and discuss the role that experimenter bias can play in influencing judgments about informal and formal linguistic experiments.1